2018
DOI: 10.1017/s0950268818002601
|View full text |Cite
|
Sign up to set email alerts
|

Use of whole genome sequencing to complement characterisation of a typhoid fever outbreak among a Marshallese community: Oklahoma, 2015

Abstract: Typhoid fever is an illness caused by Salmonella enterica serotype Typhi. In developing regions, it affects an estimated 20 million people annually, causing 200 000 deaths. Although uncommon, cases occur in the USA each year, predominantly due to international travel. During February 2015, the Oklahoma State Department of Health (OSDH) detected an outbreak of typhoid fever among residents of northwestern Oklahoma. OSDH conducted case-patient interviews to identify the source and symptomatic contacts. Whole gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…We detected from 0 to 28 pairwise SNP differences among the 12 putative epidemiologic linkages and 3 instances of repeat positive cultures from the same individual collected ~1 month apart ( Table 4 ). Relatedness criteria of 10 SNPs or less [ 40 ] would encompass 13/15 (86.7%) linkages, and 12/13 were within ≤4 SNPs, a suggested cutoff for Salmonella enterica [ 41 ]. Future studies to characterize S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We detected from 0 to 28 pairwise SNP differences among the 12 putative epidemiologic linkages and 3 instances of repeat positive cultures from the same individual collected ~1 month apart ( Table 4 ). Relatedness criteria of 10 SNPs or less [ 40 ] would encompass 13/15 (86.7%) linkages, and 12/13 were within ≤4 SNPs, a suggested cutoff for Salmonella enterica [ 41 ]. Future studies to characterize S .…”
Section: Discussionmentioning
confidence: 99%
“…We detected from 0 to 28 pairwise SNP differences among the 12 putative epidemiologic linkages and 3 instances of repeat positive cultures from the same individual collected ~1 month apart (Table 4). Relatedness criteria of 10 SNPs or less [40] would encompass 13/15 (86.7%) linkages, and 12/13 were within �4 SNPs, a suggested cutoff for Salmonella enterica [41]. Future studies to characterize S. Typhi population diversity in acute infections and asymptomatic carriers by sequencing and comparing multiple colonies obtained from stool cultures collected over time, as has been completed for other enteric pathogens [42], could aid in establishing appropriate thresholds for SNP-based relatedness among S. Typhi isolates for cluster identification.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Nearly all those contacted responded, and are included as Consortium authors on this study. The exceptions, where authors did not respond to email inquiries, were: (i) one genome reported from Malaysia (Ahmad et al, 2017) and n=133 draft genomes reported from India (Katiyar et al, 2020), which were excluded as sequence reads were not available in NCBI; and (ii) n=39 genomes reported in studies of travel-associated or local outbreaks (Burnsed et al, 2019;Hao et al, 2020;Shin et al, 2021), which were included as raw sequence data and sufficient metadata were publicly available. A further n=850 genomes sequenced by US Centers for Disease Control and Prevention and available in NCBI were excluded from analysis because travel history was unknown and most US cases are travel-associated.…”
Section: Sequence Data Aggregationmentioning
confidence: 99%
“…The most commonly implemented intervention, described in 17 (65%) of 26 outbreaks, was improving WASH infrastructure, including building a new water tower, repair of unsanitary latrines and toilets, and rehabilitation of fecally contaminated boreholes. 38,51,[57][58][59] Other measures to improve drinking water, implemented in 14 (54%) outbreaks, 32,38,39,44,47,49,57,[59][60][61][62][63][64][65] were described as improving water quality which included providing alternative drinking water sources and distribution of chlorine products for water disinfection in the household, point of use, point of water collection, or at the municipal water source. Efforts to increase health education were described in 15 (58%) outbreaks.…”
Section: Resultsmentioning
confidence: 99%